Key Influencing Factors On Ticket Purchase Decision - Zeini, Cerlis Cesar; Santoso, Adi; Riawan, Riawan (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2024)
Background – Rapid technological advances are able to change all aspects of life and consumer behavior, so that consumers often make purchasing decisions using technology such as the internet Aim – The aim of this research is to prove the influence of e-WebQual, content marketing, social media marketing variables on purchasing decisions. Design/ Methodology/ Approach - This research is quantitative research with a data collection method through questionnaires distributed using Google Form to 192 respondents using accidental sampling technique by distributing questionnaires to respondents who meet the criteria such as CGV Madiun cunsumers. Data measurement uses a Likert scale of one to 5. Data analysis in this study uses SMART PLS 3.0 Findings – The research results show that e-WebQual has a significant influence on the decision to purchase CGV Madiun tickets, content marketing has a significant influence on the decision to purchase CGV Madiun tickets, social media marketing has a significant influence on the decision to purchase CGV Madiun tickets. Conclusion - It was discovered that E-WebQual, content marketing, and social media marketing have a positive and significant impact on purchasing decisions. Research Implication – This research has important implications for consumers and the CGV Madiun company. It will be beneficial for consumers in making purchasing decisions due to rapidly developing technological advances, then it will be beneficial for the CGV Madiun company, judging from the research results, the variables e-WebQual, content marketing, social media marketing can be used to explain purchasing decisions so that they can have a positive influence on the performance of CGV Madiun Limitations – This research shows that the R-Square results show that 54.5% of the dependent variable can be explained by the independent variable, while the remaining 45.5% is influenced by other variables